New challenges in the luxury universe: an exploratory study of the concept of luxury experience in the Brazilian market from the perspective of brands and consumers: a case study of Pati Piva - Aguilera, Paola (2014)
Luxury has evolved over the centuries; new challenges have created questions of appropriate strategies for brands. Experience and authenticity became important aspects in the field: consumers are enjoying more material comfort and there is a trend of a cultural shift for personal fulfillment and aspiration through experience. The biggest challenge for today's luxury marketers is to not only talk to the target, but to understand how the target is shifting, while not alienating consumers and damaging the brand´s image. Considering managers and consumers perspectives separately, it would be possible to conclude that their perceptions are congruent, as many studies have presented. However, if perspectives are put together and compared, different realities could emerge. This exploratory research is based on a case study that describes both perspectives of their perception on luxury experience, consumer behavior and consumption motivations, and luxury retailing. It was developed interviews with the brand owner and 10 brand´s consumers, and also indirect observations in the brands distribution formats. In the brand perspective, the case study has shown that luxury experience involves the construction of brand experience strategy based on products, multiple retail channels, consumer engagement, personal activity, exploration of five senses and other forms. In the consumer´s perspective, results revealed that brand consumers interviwed have different luxury experience perceptions and expectations; however, what is common is that service and quality must be maintained and they reflected the overall experience. Additionally, luxury retailing influences directly the consumer´s perception that must integrate multiple channels to fulfill personal demands. The research makes contributions for both actors - brand and consumer, in the sense that translates theoretical concepts of the experience itself and tries to clarify aspects that are still unknown and explored through the exploration of ways to detect the alignment between brand and consumer expectations of the experience.